The Post‐Merger Performance of Acquiring Firms: A Re‐examination of an Anomaly - AGRAWAL, ANUP; JAFFE, JEFFREY F.; MANDELKER, GERSHON N. (Journal of Finance, 1992)
ABSTRACT The existing literature on the post‐merger performance of acquiring firms is divided. We re‐examine this issue, using a nearly exhaustive sample of mergers between NYSE acquirers and NYSE/AMEX targets. We find that stockholders of acquiring firms suffer a statistically significant loss of about 10% over the five‐year post‐merger period, a result robust to various specifications. Our evidence suggests that neither the firm size effect nor beta estimation problems are the cause of the negative post‐merger returns. We examine whether this result is caused by a slow adjustment of the market to the merger event. Our results do not seem consistent with this hypothesis.